Development, certification, and use of a pharmacopoeial standard for the content of immunoglobulin A in human immunoglobulins for parenteral administration - A. V. Nechaev; E. Yu. Kudasheva; E. L. Postnova; R. A. Volkova; O. V. Fadeikina; I. V. Borisevich; A. A. Movsesyants (Биопрепараты: Профилактика, диагностика, лечение, 2023)
Scientific relevance. The immunoglobulin A (IgA) impurity content in parenteral human immunoglobulins should be determined in accordance with the State Pharmacopoeia of the Russian Federation by kinetic nephelometry, radial immunodiffusion, or enzyme immunoassay (ELISA) with a reference standard. The International Standard (IS) for the content of IgA is certified using gravimetry and radial immunodiffusion. However, neither of the existing standards for  the content of IgA in human immunoglobulins is currently certified using all three compendial methods. This prevents analysts from comparing test results obtained by different methods  and may lead to an underestimation of the IgA content in human immunoglobulins.Aim. This study aimed to determine the procedure for the development, certification, and use of a pharmacopoeial reference standard (RS) for the content of IgA in human immunoglobulins.Materials and methods. The authors studied candidate RSs for the IgA content derived from human plasma for fractionation. The IgA content determination involved kinetic nephelometry, radial immunodiffusion, and ELISA, as well as commercial test kits and the IS. The authors quantified the IgA impurity in samples of commercial human immunoglobulins from various manufacturers. The data analysis involved descriptive statistics and variance analysis using Microsoft Excel and Statistica 10.Results. The  authors  established  a  pharmacopoeial  standard  with  a  certified  IgA  content  of 1.98 mg/mL (expanded uncertainty, 0.44 mg/mL; coverage coefficient, k=2; confidence level, 95%) for IgA impurity quantification in human immunoglobulins by radial immunodiffusion and ELISA and that of 1.31–2.64 mg/mL (expanded uncertainty, 0.67 mg/mL; coverage ratio, k=3; confidence level, 99%) for intralaboratory quality control of IgA impurity quantification by kinetic nephelometry, radial immunodiffusion, and ELISA.Conclusions.  The  pharmacopoeial  standard  developed   in   the   study   has   been   included in the register of standards of the State Pharmacopoeia of the Russian Federation as the Reference Standard for the Content of Immunoglobulin Class  A  (IgA) (Registry  No.  3.1.00454). The pharmacopoeial standard is intended for the standardisation of analytical methods for the-determination of the IgA impurity content in parenteral human immunoglobulins.